Ethnoscience and Ethnobotanical: The Construction of Indigenous Knowledge on Parijoto (Medinilla speciosa) Plant - Ulya Fawaida; Sudarmin Sudarmin; Sigit Saptono; Saiful Ridlo (Journal of Natural Science and Integration, 2025)
Parijoto fruit (Medinilla speciosa), a characteristic plant from the slopes of Mount Muria, is traditionally believed to enhance fertility in pregnant women. This study aimed to examine the process of making parijoto syrup and relate it to scientific concepts. A qualitative case study approach was employed, involving semi-structured interviews, field observations of syrup production, and literature review to explore the fruit’s composition and benefits. The research stages included preparation, primary data collection, and data analysis. Data were analyzed descriptively and comparatively, linking indigenous knowledge with principles of ethnoscience and ethnobotany. The investigation focused on community practices in syrup preparation, followed by verification, reconstruction, formulation, and conceptualization into scientific knowledge. From a scientific perspective, the syrup production process illustrates concepts such as classification of living organisms, elements and compounds, energy and work, simple machines, mixtures, temperature and heat, and energy transfer. Ethnobotanical findings show that the local community uses parijoto fruit and leaves for various medicinal purposes and fertility enhancement, with cultural beliefs attributing positive effects on offspring appearance. Integrating local knowledge with scientific learning provides opportunities to foster meaningful understanding and strengthen connections between education and regional natural potential.Keywords: parijoto plant, medinilla speciosa, ethnoscience, ethnobotanical, indigenous knowledge